2001
DOI: 10.1007/s002210100694
|View full text |Cite
|
Sign up to set email alerts
|

Hand trajectory invariance in reaching movements involving the trunk

Abstract: Movements of different body segments may be combined in different ways to achieve the same motor goal. How this is accomplished by the nervous system was investigated by having subjects make fast pointing movements with the arm in combination with a forward bending of the trunk that was unexpectedly blocked in some trials. Subjects moved their hand above the surface of a table without vision from an initial position near the midline of the chest to remembered targets placed within the reach of the arm in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 56 publications
12
64
1
Order By: Relevance
“…Similar conclusions have been reached in earlier studies of trunk-assisted reaching (Adamovich et al 2001;Ma and Feldman 1995). In those studies, different trajectories in the joint configuration space were observed that maintained relative consistency of the endpoint trajectory depending on whether the trunk contributed to the movement or the trunk motion was mechanically blocked.…”
Section: The Ucm Concept and Stability Of Actionsupporting
confidence: 86%
“…Similar conclusions have been reached in earlier studies of trunk-assisted reaching (Adamovich et al 2001;Ma and Feldman 1995). In those studies, different trajectories in the joint configuration space were observed that maintained relative consistency of the endpoint trajectory depending on whether the trunk contributed to the movement or the trunk motion was mechanically blocked.…”
Section: The Ucm Concept and Stability Of Actionsupporting
confidence: 86%
“…Studies have also pointed out the relationship between trunk and upper-limb coordination when the target is located either at arm's length [35] or beyond arm's length [36][37]. Trunk movements were minimal when the target could be reached at arm's length; however, for objects located out of arm's reach, trunk motion contributed significantly to the transport phase of the hand.…”
Section: Discussionmentioning
confidence: 99%
“…The vestibular system contributes to arm-trunk coordination during reaching (Adamovich et al 2001;Mars et al 2003) and is sensitive to the biomechanical constraints of the task (Tunik et al 2003). In the absence of visual and proprioceptive feedback, vestibulospinal contribution was primarily evident during reaching toward an ipsilateral target as opposed to a contralateral target (Tunik et al 2003).…”
Section: Discussionmentioning
confidence: 99%